HUBUNGAN KESEIMBANGAN TUBUH DAN POWER OTOT LENGAN TERHADAP KEMAMPUAN SERVIS ATAS DALAM PERMAINAN BOLA VOLI PADA SISWA PUTRA EKSTRAKULIKULER SMAN 1 ALAS BARAT TAHUN 2017 - Ertandi, Ertandi; Yusuf, Rusdiana; Ahmad, Noor (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
In playing volleyball, some athletes were still lack in the ability to perform overhead service so that it was considered as the aim this study, i.e. to determine the correlation between the body balance and arm muscles power toward the overhead service ability in volleyball on male extracurricular students of SMAN 1 Alas Barat in 2017. To obtain the data in this study, it was conducted performance test as the principal method while documentation was as an auxiliary method. The analysis of statistical data with multiple linear correlation formula with the research design used is a correlation samples (sample dependent) with a sample of 20 students. Based on data analysis to answer the hypothesis of the proposed research, the value of r-score is equal to 20.140 with a significance level of 5%, and N = 20 obtained r-table of 0.444. Thus, r-score was higher than r-table (20.140 > 0.444), which meant that there was correlation between the body balance and arm muscles power toward the overhead service ability in volleyball on male extracurricular students of SMAN 1 Alas Barat in 2017